2006
DOI: 10.1136/jcp.2005.029272
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of connexins 26 and 43 in lymph node metastases of breast cancer

Abstract: Background: Gap junctions are intercellular channels composed of connexins, which mediate the direct passage of small molecules between neighbouring cells. They are involved in regulation of cell cycle, cell signalling, and differentiation, and probably invasion and metastasis. The role of connexins in the metastatic process is controversial, because some studies indicate that connexin expression is inversely correlated with metastatic capacity. In contrast, others demonstrate that connexins may be involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
154
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(176 citation statements)
references
References 31 publications
17
154
1
4
Order By: Relevance
“…Kamibayashi et al [36] demonstrated that even though the expression of Cx26 and Cx43 was reduced in the early stages of mouse skin carcinogenesis, both connexins were expressed on the plasma membranes of cells invading the lymph nodes. Similar observations were made for breast cancer [35], prostate cancer [37,38] and glioma cell populations [39]. In melanoma cells residing in the basal layer, Cx26 levels remained unchanged, but were significantly up-regulated in the cells invading the dermis.…”
Section: The Effect Of Gap Junctions On the Invasive Potential Of Tumsupporting
confidence: 68%
See 1 more Smart Citation
“…Kamibayashi et al [36] demonstrated that even though the expression of Cx26 and Cx43 was reduced in the early stages of mouse skin carcinogenesis, both connexins were expressed on the plasma membranes of cells invading the lymph nodes. Similar observations were made for breast cancer [35], prostate cancer [37,38] and glioma cell populations [39]. In melanoma cells residing in the basal layer, Cx26 levels remained unchanged, but were significantly up-regulated in the cells invading the dermis.…”
Section: The Effect Of Gap Junctions On the Invasive Potential Of Tumsupporting
confidence: 68%
“…Thus, a deregulation of the mechanisms determining cell proliferation is followed by the acquisition of the ability of unrestricted migration by tumour cells, a prerequisite of invasion [34]. Although a correlation between the loss of gap junctions and the metastatic capability of cancerous cells was reported (see [35]), several studies have revealed relatively high levels of connexins and gap junctional coupling in populations of invasive tumour cells. Kamibayashi et al [36] demonstrated that even though the expression of Cx26 and Cx43 was reduced in the early stages of mouse skin carcinogenesis, both connexins were expressed on the plasma membranes of cells invading the lymph nodes.…”
Section: The Effect Of Gap Junctions On the Invasive Potential Of Tummentioning
confidence: 99%
“…Connexins are typically localized in the cell membrane and normally show a punctate pattern of expression [21,22]. Aberrant localization of connexins was revealed in several types of tumours in our and other studies [15,20,23,24] and it might result in the intercellular communication loss via gap junction channels. In the present study, we demonstrated changes in the Cx26 expression and localization, which manifested in decreased expression and mainly cytoplasmic localization of this protein in the endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 87%
“…Different studies indicated that Cx26 may be involved in tumour cell invasion and metastasis. Kanczuga-Koda et al (19) described Cx26 overexpression in corresponding LNMs compared with primary mammary carcinoma. Saito-Katsuragi et al (17) demonstrated a significant Cx26 expression in tumour cells and tumour-related microvessel endothelia during metastasis of human malignant melanoma, whereas no Cx26 expression was found in control tissues from either healthy dermis or nevus cell nevi.…”
Section: Descriptive ------------------------------------------------mentioning
confidence: 99%
“…Cx26 was identified in melanoma cells and surrounding small vessel endothelia (17), as well as in squamous cell lung carcinoma and its associated lymph node metastases (LMNs) (18). Cx26-and Cx43-negative primary breast cancers developed Cx26-and Cx43-positive LMNs (19). Glioma cells establish functional gap junctions comprising Cx43 with astrocytes in the adult brain, thus facilitating direct parenchymal invasion (20).…”
Section: Introductionmentioning
confidence: 99%